[2+2] Cycloadditions of Methylene exo‐Glycals: Synthesis of Glycopyranosylidene‐Spiro‐Azetidine‐2‐ones (β‐Lactams) and Cyclobutanones. Issue 12 (23rd February 2023) - József, János; Somsák, László; Tóth, Marietta; Juhász, László
Abstract: [2+2] Cycloadditions of methylene exo ‐glycal derivatives with chlorosulfonyl isocyanate and dichloroketene were studied in detail, investigating the effect of the carbohydrate moiety, protecting groups as well as reaction temperature on the yields of the transformations. These reactions gave new anomeric spiro‐β‐lactam and spiro‐cyclobutanone derivatives, whose structure was established by 1D and 2D NMR and MS experiments. The transformation of spiro‐cyclobutanone into spiro‐γ‐lactone was also demonstrated. Abstract : New anomeric spiro‐β‐lactam and spiro‐cyclobutanone derivatives were synthesized by [2+2] cycloadditions of methylene exo ‐glycals with chlorosulfonyl isocyanate and dichloroketene. The reactions were studied in detail, investigating the effect of carbohydrate moiety, protecting groups as well as reaction temperature on the yields. The transformation of spiro‐cyclobutanone into spiro‐γ‐lactone was demonstrated.